GUT MICROBIOTA AND DIABETES MELLITUS - AN INTERLINKAGE - Rp, Jayaswal; M, Vijayasimha; Pk, Prabhakar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Â In recent years, the curiosity to investigate the relationship between gut microbiota and diabetes development has increased. Evidence from previous studies suggests that gut microbiota manipulation may assure to prevent diabetes development in future, primarily in susceptible individuals. Here, we reviewed special gut microbiota types proposing development of Type 1 (T1D) and Type 2 diabetes (T2D) in humans and laboratory animals. The available data we found are still inconclusive and required more attention in discriminating specific groups of gut microbiomes strongly indicating T1D and T2D development or prevention. Further, we suggested for the first time to study the gut microbiota in different ways to find the root cause of diabetes development.